2018
DOI: 10.1097/md.0000000000011902
|View full text |Cite
|
Sign up to set email alerts
|

STROBE—A preliminary investigation of IVIM-DWI in cardiac imaging

Abstract: This study aims to explore the possibility to apply intravoxel incoherent motion-magnetic resonance imaging (IVIM-MRI) in cardiac imaging.Multi-b-value diffusion-weighted imaging (DWI) sequence scanning was performed on 12 healthy volunteers. A double exponential model was adopted, and the b-value sequence was 0, 20, 60, 80, 120, 200, and 600 second/mm2. The D-value, D∗-value, and f-value of the anterior posterior and lateral walls of the ventricular septum were respectively measured on the short axis section … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Nevertheless, the complexity of cardiac anatomy and physiological movement affects the image quality in the DWI, which in turn affects the accuracy of IVIM-DWI parameters. In this experiment, iShim sequence was used for the IVIM-DWI imaging, which is an improvement in the traditional EPI sequence compared with the traditional DWI 7 . In comparison with the conventional single-shot EPI sequencing, the advantages of the iShim sequencing lie in the facts that: (1) corresponding b-values can be selected reasonably according to the requirements of the experiment, especially when the b-values are small, so as to improve the fitting accuracy of the D* value 8 ; (2) it can reduce image distortion; the iShim sequence scans a B0-Map before scanning each slice, and the signal changes of the B0-Map are used to correct the distortion of EPI, thereby contributing to the improvement in the distortion caused by the heterogeneity of the main magnetic field; (3) it can exert a better fat-suppression effect; specifically, the sequence can achieve a more thorough suppression of fatty tissue signals, by improving the accuracy of fat-selective pulses and using a slice-selection gradient-reversal fat-suppression technique; (4) it optimises the image acquisition mode, allows higher acquisition times, increases the signal-to-noise ratio and further improves the accuracy of parameter fitting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the complexity of cardiac anatomy and physiological movement affects the image quality in the DWI, which in turn affects the accuracy of IVIM-DWI parameters. In this experiment, iShim sequence was used for the IVIM-DWI imaging, which is an improvement in the traditional EPI sequence compared with the traditional DWI 7 . In comparison with the conventional single-shot EPI sequencing, the advantages of the iShim sequencing lie in the facts that: (1) corresponding b-values can be selected reasonably according to the requirements of the experiment, especially when the b-values are small, so as to improve the fitting accuracy of the D* value 8 ; (2) it can reduce image distortion; the iShim sequence scans a B0-Map before scanning each slice, and the signal changes of the B0-Map are used to correct the distortion of EPI, thereby contributing to the improvement in the distortion caused by the heterogeneity of the main magnetic field; (3) it can exert a better fat-suppression effect; specifically, the sequence can achieve a more thorough suppression of fatty tissue signals, by improving the accuracy of fat-selective pulses and using a slice-selection gradient-reversal fat-suppression technique; (4) it optimises the image acquisition mode, allows higher acquisition times, increases the signal-to-noise ratio and further improves the accuracy of parameter fitting.…”
Section: Discussionmentioning
confidence: 99%
“…IVIM can reflect the diffusion and perfusion of living tissues through multi-parameter measurements. Therefore, IVIM may play an important supplementary role to conventional CMR in patients with heart disease who cannot tolerate drug therapy 7,8 . We hypothesized that the IVIM-DWI had a good value in diagnosing old myocardial infarction and myocardial fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Mou et al [ 14 ] found that the left ventricular myocardium of patients with HCM was significantly lower than the D ∗ myocardium of healthy people, indicating that the myocardium of HCM patients had low perfusion injury, which suggested that IVIM imaging was helpful for the prediction and monitoring of myocardial microcirculation. Xiang et al [ 15 ] confirmed different myocardial perfusion parameters in different coronary artery blood supply areas via IVIM imaging. Finally, An et al [ 16 ] showed that the D ∗ and f values decreased significantly in the myocardial infarction area, while the D value showed a downward trend after PCI.…”
Section: Discussionmentioning
confidence: 99%
“…(11) and Xiang et al. (15) included 12 healthy volunteers; Moulin et al. (16) included 10 healthy volunteers; and Rapacchiet et al.…”
Section: Introductionmentioning
confidence: 99%